Kinerja Dinas Perindustrian Dan Perdagangan (DISPERINDAG) Dalam Video Informasi Untuk Memberdayakan Industri Kecil Dan Menengah Di Kabupaten Tangerang - Ari Eviawan; Falday Kurniawan; Akhirul Agustian (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
The current openness allows access to information information can be easily retrieved whenever and wherever. The information is important, because with information people will get all it wants. Dissemination of information is spread through the media print shaped electronic media atupun multimedia, from the media that the public can obtain information. Department of industry and trade (Disperindag) is one of the Government agencies fields of industry and commerce, Service industry and trade (Disperindag) which is new and still use the spoken and written media, education and exhibition website but the less effective media to inform and introduce the Department of industry and trade (Disperindag), the Department of industry and trade (Disperindag) in need of video media information to support a variety of activities such as informing the public at large to medium size businesses that intend to show the efforts of medium or home industry. On the concept of there stages of preproduction, production and postproduction. In order for video-based media design producing good information and good quality used applications supporting adobe photoshop CS3, Adobe Premiere CS3 and afterb effek CS3.